Structural characterization and corrosion properties of electroless processed NiPMnO2 composite coatings on SAE 1015 steel for advanced applications - O.S.I. Fayomi (Journal of Science: Advanced Materials and Devices, 2019)
In recent years, electroless NiP coatings with the incorporation of metallic oxides have received profound interest due to their unique properties and ability to enhance the operational performance of the base metal. These coatings have been utilised for numerous applications such as aerospace, automotive and industrial field where materials with exceptional qualities are required. This present work focuses on the improvement of the surface characteristics of mild steel via the electroless deposition of NiPMnO2. The deposition was achieved by varying the mass concentration of MnO2 at fixed temperature and deposition time of 85 °C and 20 min, respectively. The examinations of the coated surfaces using Scanning Electron Microscope revealed that the surface morphology of the coated steel improved as the mass concentration of MnO2 increases. Linear potentiodynamic polarization experiments unveiled that NiPMnO2 coating exhibits good corrosion resistance, protecting the steel from the penetration of corrosive ions in the test medium. Moreso, the investigation of the microhardness behaviour of the coated samples using the Vickers hardness tester shows that NiPMnO2 coating enhanced the microhardness of the steel substrate. Keywords: Electroless, Coating, Morphology, Corrosion, Hardness